Current status and future directions of cardiac rehabilitation program: a review of the literature - Sutantri Sutantri (Journal of Health Technology Assessment in Midwifery, 2019)
One of the effective treatments for patients recovering from acute cardiac illness or surgery is cardiac rehabilitation (CR). CR has proven to be effective to reduce mortality, morbidity, and also to improve the quality of life. The purpose of this review is to present the current status of CR program worldwide as well as to identify a potential approach for further investigation. Literature searching of electronic databases was conducted in several databases including CINAHL, MEDLINE, PsycINFO, and EMBASE, and Google Scholar. CR aims to restore patients with CVD to a state of good health. Each country has different approach in the provision and organization of CR as well as the allocation of resources, which depends on their health policies and politics. The indications for CR also differ between countries, but traditionally CR has been used following acute myocardial infarction (MI). CR programs have been divided into three phases of progression. Hospital-based or supervised site-based programs have been known as the most common model of CR in most countries. The core components of CR include patient assessment, nutritional counselling, exercise training, physical activity counselling, weight management, tobacco cessation, aggressive coronary risk-factor management, and psychosocial management. Despite the apparent benefits of CR in patients with CVD, these programs remain largely underused. The participation rates in the USA, Australia, and Europe are low, estimated at 10-30%. New research areas that explore new ways of CR delivery to improve referral and participation rates are essential.